ASSESSMENT OF THE ECOLOGICAL STATE OF THE TOBYL RIVER BASED ON HYDROCHEMICAL INDICATORS (Eurasian Journal of Ecology, 2026)
This article presents a comprehensive assessment of the ecological state of the Tobyl River within the territory of Kostanay Region based on hydrochemical indicators for the period 2020–2024. The study is based on observation data from the Kostanay branch of RSE “Kazhydromet”, where water samples were collected at five points along the river. Key indicators such as calcium, magnesium, chlorides, mineralization, and suspended solids were analyzed to evaluate water quality. According to the Unified Water Quality Classification System, the analysis results showed that water at all sampling points falls into Class 6 — a highly polluted category. This indicates the water is unsuitable for drinking, domestic, and fishery use. Additionally, a correlation analysis was conducted to identify relationships between the indicators, revealing strong correlations among calcium, magnesium, mineralization, and suspended solids, and a weak correlation with chlorides. The findings of the study indicate a high level of anthropogenic pressure within the Tobyl River basin and highlight the urgent need for measures to restore the aquatic environment.Keywords: Tobyl River; ecological state; hydrochemical indicators; water quality; mineralization; correlation analysis; anthropogenic pollution; water monitoring; Kostanay Region; sustainable water use.